AZATHIOPURINE INDUCED HISTOLOGICAL CHANGES IN LIVER IN RABBIT MODEL - Khoharo, Haji Khan; Talpur, Mozna; Siddiqui, Shomail; Bhurgri, Ali Nawaz (Pakistan Journal of Physiology, 2015)
Objective: To evaluate azathioprine (AZA) induced liver injury and protective effects of Zinc sulphate (Zn) and L Ascorbic acid (AA) in rabbit model. This experimental-analytical study was carried out at animal house of Isra University, Hyderabad from July 2013 to November 2014. Methods: One hundred rabbits were selected through inclusion and exclusion criteria. Group 1 (Controls, n=20) were given 0.9% isotonic saline orally, Group 2 (n=20) AZA, Group 3 (n=20) AZA+Zn, Group 4 (n=20) AZA+AA and Group 5 (n=20) AZA+Zn+AA orally for 4 weeks. At end of 4th week, the rabbits were sacrificed. Abdomen was incised in midline and liver was removed, fixed in 4% formaldehyde and was paraffin embedded. 5 micron thick liver tissue sections were stained with Haematoxylin & Eosin. Data was completed using Statistix 8.1 and Chi-square test, and pâ‰¤0.05 was taken as significant. Results: The liver histological findings showed significant differences among the controls, AZA, AZA+Zn, AZA+AA and AZA+Zn+AA (p=0.001). AZA induced severe liver injury. Zn and AA treated rabbits showed improvement in liver histology. AZA induced changes includes hepatocytes necrosis parenchyma regenerative nodular hyperplasia, peri-sinusoidal and sinusoidal dilation, cholestasis and peliosis hepatis. Disarray of hepatocytes cords was observed. Hydropic changes with central venule congestion and sinusoid congestion was visible. Conclusion: Azathioprine produces severe liver injury. Liver histology was improved with concomitant administration of zinc and ascorbic acid.